Gambaran Hipokromasi Eritrosit dan Mean Corpuscular Hemoglobin (MCH) pada Penderita Ginjal Kronis di RSUD Kraton Kabupaten Pekalongan - Subur Wibowo; Fitrianingsih Fitrianingsih; Muhamad Salasa Dis Nahari (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
The prevalence of Chronic Kidney Disease (CKD) in Indonesia in 2013-2018 has increased from 0.2% to 0.38%. Patients with CKD have low erythropoietin, so that the production of erythrocytes is disrupted and causes anemia. Anemia in CKD includes the type of normocytic-normochromic. Hypochromic occurs because iron reserves cannot be used in the process of erythropoiesis, resulting in decreased synthesis of hemoglobin. Erythrocytes will appear pale on the peripheral blood smear. Hypochromic is clinically associated with iron deficiency anemia. Changes in the color of the erythrocytes also indicate a state of immaturity of the cells, which causes erythrocyte hypochromacy. This study aims to determine MCH levels and erythrocyte hypochromatous abnormalities in patients with chronic kidney disease on hemodialysis therapy at Kraton Hospital, Pekalongan Regency. The research method used is descriptive, namely the type of research that describes the phenomenon of the object under study in the form of a narrative. The results of the analysis of the MCH values in the normal category were 25 samples (71.4%), the MCH values in the low category were 10 (28.6%). There were 9 samples (25.7%) of mild hypochromacy in the mild hypochromic category, 15 (42.9%) of moderate hypochromic category, 11 (31.4%) of severe hypochromic category. So it can be concluded that the MCH values in the normal category are more than in the low category and hypocracy in the moderate category is more than mild and severe hypochromacy.